Cases of management of paediatric tubo-ovarian torsion - Bhandari, Ruchi; Khemani, Manju; Mustafa, Asif (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Ovarian torsion is the fifth most common cause of gynaecologic surgical emergency. It warrants early diagnosis as timely surgical management will avoid the further adnexal injury. In paediatric population, this is especially dangerous as the condition can go undiagnosed because of its rarity and nonspecific presentation. This leads to delay in surgical exploration and loss of ovarian function. In these cases, the ovary and often the ipsilateral fallopian tube twist with the vascular pedicle, resulting in vascular compromise. Unrelieved torsion leads to haemorrhagic infarction. We encountered 3 cases of ovarian torsion in paediatric age group during a period of 12 months. All cases presented with acute pain abdomen for 3-7 days period with loss of appetite and unable to pass motion with varied disappearance of pain. On ultrasound all the cases were diagnosed with ovarian cyst with torsion and underwent laparoscopic cystectomy. This case series is written just to show the results of de-torsion and conserving the fallopian tube and ovary after vascular damage. This type of conservative management may give chance to ovary to return to viability. This was seen in all 3 cases dealt by us on repeat scan on follow up. Even on de-torsion if ovary does not regain its colour immediately it should be conserved, and cystectomy should be performed rather than oophorectomy. Conservative surgery, in the form of ovarian de-torsion can be tried in cases of ischemia but if ovarian necrosis has occurred, then salpingo-oophorectomy is performed as the last resort.